Multi-drug resistant tuberculosis - Yasinskiy, R. M.; Solodovnik, Yu. S.; Ясінський, Роман Миколайович; Солодовник, Юрій Семенович (Zaporozhye state medical university, 2015)
The study guide is made according to the work program of phthisiology for students – foreign citizens of 6 courses for practical classes. The manual described the epidemiological situation of multi-drug resistant tuberculosis in the world, the basic concepts and terms from the topic, medicines to treat multi-drug resistant tuberculosis and patients’ treatment regimens.